2022
DOI: 10.1590/fst.82721
|View full text |Cite
|
Sign up to set email alerts
|

The fruit of peach palm (Bactris gasipaes) and its technological potential: an overview

Abstract: The Amazon hosts numerous fruit species, which are consumed by the local population and distributed by the local economy in the commerce markets, but most of them are unknown to the general population. Therefore, for a better understanding of the Amazon biome, the main objective of this review was to describe the physicochemical, nutritional and biological characteristics of the peach palm, highlighting its antioxidant potential. The peach palm tree is considered a polyvalent palm native to tropical Latin Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…The oil extraction yield (OY%) was investigated by dividing the extracted oil weight by the total fresh weight of the pupunha according to equation (1).…”
Section: Oil Extraction Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil extraction yield (OY%) was investigated by dividing the extracted oil weight by the total fresh weight of the pupunha according to equation (1).…”
Section: Oil Extraction Yieldmentioning
confidence: 99%
“…With its popularization, mainly of its palm heart for the rest of Brazil, it has been more studied and consumed in its most varied forms, being able to produce byproducts, such as flour for addition in gastronomy or the use of its oil for culinary and study purposes. Peach palm is found in the most diverse shapes and colors, where its chemical content varies according to the type of peach palm [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review, showed that the oil from the pupunha fruit has very interesting properties: it is liquid at room temperature and less prone to oxidation when compared to other oils with a higher concentration of linoleic acid (Costa et al, 2022).…”
Section: Characterization Of the Oil In Peach Palm Flourmentioning
confidence: 99%
“…Amazonian fruits are well known for their bioactive potential, stemming from their carotenoid contents (Anunciação et al, 2019) . Peach palm is currently the most studied Amazonian fruit, with high potential to be incorporated in food formulations (Martínez-Girón et al, 2017;Pires et al, 2019b;Costa et al, 2022). Buriti is still underexploited, while tucumã, taperebá, and araçá-boi remains still unexploited, despite their high promising content of natural pigments (Aniceto et al, 2017;Avila-Sosa et al, 2019;Pires et al, 2019a).…”
Section: Tucumãmentioning
confidence: 99%